Hallyu pop culture and the motivation of generation z in visiting South Korea - Irsan, Dimas Maulana; Khadijah, Ute Lies Siti Khadijah; Saefullah, Kurniawan; Novianti, Evi (Universitas Bunda Mulia, 2024)
Popular culture is known to have an influence in building human behavioral intentions. Moreover, now, popular culture from South Korea or often referred to as